Late Pleistocene-Recent marine malacological assemblages of the Colorado River delta (south of Buenos Aires Province): Paleoecology and paleoclimatology - Charo, Melisa Paola (2015)
The most recent Quaternary marine transgressions are well represented along the South Atlantic coast. In the Colorado River delta (39°15'S-39°55'S), south of Buenos Aires Province these deposits are mostly littoral ridges and tidal plains with abundant fossil marine fauna. Seventeen localities were analyzed (five Pleistocene, seven Holocene and five modern ones) representing the Interglacials ≥ MIS 9, MIS 5e and MIS 1. A total of 51 species were recorded (29 bivalves and 22 gastropods), together with nine micromolluscs. MIS 1 and the modern coast (37 and 42 species respectively) are the richest ones in species, unlike MIS 5e and MIS 9 (18 and 2 species respectively). In ≥MIS 9, the most abundant species is Pitar rostratus. MIS 5e and MIS 1 have in common the presence and abundance of the gastropod Heleobia australis and the bivalve Tagelus plebeius, as typical fauna of low energy environments, being the bivalve Glycymeris longior and the gastropods Bostrycapulus odites and Buccinanops globulosus common species in both kinds of marine deposits. Approximately 90% of bivalves and 75-71% of gastropods of the marine fauna are recorded from MIS 5e to the present. According to the different descriptive analyses (Bray-Curtis Index and AC) the molluscan fauna was grouped in two and five assemblages respectively, defined by age, type of deposit, and presence and/or abundance of species. Marine species represented in the area of the Colorado River delta vary in abundance among the interglacials but not in faunal composition. One of the possible causes would be the global climatic changes (e.g., rise of sea surface temperature SST) and the heterogeneity of habitats that would have conditioned the development of the different faunal assemblages during the Quaternary.